PERANAN SISTEM IMUNITAS MELAWAN INFEKSI TUBERKULOSIS PARU-PARU - Widaninggar Rahma Putri (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Tuberculosis, an infectious disease caused by Mycobacterium tuberculosis evoked more than 1 million mortality every year and infected more than a quarter population worldwide. Host immunity systems against tuberculosis provided by innate immunity and adaptive immunity. Molecules and cells in both of immunity systems undertaking this mechanism and initiate each other facing infection from very first bacterial exposure inside the host. Immunity systems against bacteria development from inhalation step through granuloma initiation and antibody anti-tuberculosis. Host’s mechanism against tuberculosis is urge to presumed in order to develop strategies based on immunology to decreasing tuberculosis incidence worldwide